UTILIZING INTERACTIVE ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE AND SCIENCE IN SELECT SOUTHEAST ASIAN CLASSROOMS - Villarama, Joseph A; Cruz, Lyan Mae Micah V Dela; Barcelita, Karen Jean; Fitriani, Irma; Techakosit, Somsak (LPPM Universitas Jambi, 2025)
The proliferation of interactive artificial intelligence (AI) in the academic sphere maneuvers the steering of teaching and learning processes, which transfigures the roles of teachers and learners today. This study explored the perspectives and experiences of teachers and students in select Southeast Asian countries on the challenges and opportunities they faced in utilizing interactive AI. A qualitative narrative research approach was employed, following a series of scheduled semi-structured hybrid interviews, using a set of 10 content-validated interview guide questions, with 60 participants chosen through a non-probability sampling technique. After a rigorous thematic-narrative analysis, findings revealed capitalizing on the essential presence of interactive AI in education; however, there is a strong drive to establish clear policy guidelines that address ethical and fair access to AI in classrooms. Further, interactive AI customized learning and managed teachers’ workloads; nevertheless, both should balance the utilization of interactive AI in their work. In view of equitable and inclusive education, ensuring equity in personalized learning with the use of interactive AI must be fostered. Conversely, problems included unequal access, ethical issues, and over-reliance on technology—all of which call for thoughtful planning and policy-making. Unless carefully implemented, interactive AI risks exacerbating existing inequities or undermining human contacts that lie at the heart of quality teaching and learning. This study underlines the need to blend the strengths of interactive AI with the irrepressible value of teacher-student interaction and tradition-based approaches. By promoting equity, transparency, and collaboration, interactive AI complements, but does not replace, the significant role of educators.